PENGARUH VARIASI VOLUME LIMBAH SERBUK KAYU MAHONI DENGAN PERLAKUAN ALKALI TERHADAP KEKUATAN MEKANIK DAN MIKROSTRUKTUR KOMPOSIT PARTIKEL - fatmawati hendrik fatma; Rita Desiasni; Fauzi Widyawati (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
The strength of the mechanical and physical properties of particle composite materials is influenced by the volume fraction of the powder and matrix. Fraction variations used are 30:70%, 50:50%, and 70:30% with the hand lay up method. The pretreatment was carried out by soaking 2% NaOH for 1 hour. The results of the MOE treatment mechanical test received the highest test value at the powder volume fraction of 30:70%, which was 6145.51 kgf/cm² and the highest MOR test value at the 30:70% volume fraction, which was 167.38 kgf/cm². Meanwhile, the highest non-treatment MOE value at the 30:70% powder volume fraction was 5540.9 kgf/cm² and the highest MOR test value at the 30:70% volume fraction was 156.6 kgf/cm². The results of the physical properties test were the highest density at the 30:70% powder volume fraction of 0.87 gr/cm³ and the highest density at the 30:70% non-treatment powder volume fraction of 0.78 gr/cm³. The results of the MOE mechanical test do not meet the JIS A 5908-2003 standard while the MOR mechanical test and physical test have met the JIS A 5908- 2003 standard. The results of microstructure testing showed that at a fraction of powder volume of 30:70% it was seen that the particles were coarser which blended perfectly with the matrix. Meanwhile, in the volume fraction of non-treatment powder 30:70% it looks finer particles and powders with a matrix seem to not glue well, this is because of the wax coating on the powder.